The importance of artificial intelligence and socio-economic justice standards - Alimov Nasimjon Hoshimovich (Genius Journals, 2025)
This article analyzes the role, opportunities and existing risks of artificial intelligence (AI) technologies in ensuring socio-economic justice. In particular, special attention is paid to the issues of compliance with the principles of equality, transparency and accountability in decision-making processes based on AI. International experience and legal and institutional aspects of the use of AI in developing countries, including Uzbekistan, are also considered. The advantages and problems of implementing AI systems in the conditions of the Uzbek economy are analyzed. The results of the study show that management approaches based on artificial intelligence are an important factor in increasing sustainable economic growth and efficiency.
Keywords: artificial intelligence; social justice; economic equality